An Introduction to Grammar: Traditional, Structural, Transformational - LaPalombara, Lyda E. (Winthrop Publishers, 1976)
Keywords: English language; Grammar, Generative; Grammar; English language; award_winner; dept.eng; faculty_collection

Off to See the Wizard - Ort, Daniel (Mason/Charter, 1975)
Keywords: dept.eng; faculty_collection

Caroline M. Kirkland, - Osborne, William S. (Twayne's United States authors series ; TUSAS 207, 1972)
Keywords: 19th century; Criticism and interpretation; Women and literature; History; Kirkland, Caroline M. (Caroline Matilda), 1801-1864; United States; dept.eng; faculty_collection

Hemingway and the Sun Set, - Sarason, Bertram D. (NCR Microcard Editions, 1972)
Keywords: Hemingway, Ernest, 1899-1961. Sun also rises; dept.eng; faculty_collection

The Luck of Barry Lyndon. - Thackeray, William Makepeace; Anisman, Martin F. (University Press, 1970)
Keywords: Europe; Fiction; Fiction; Rogues and vagabonds; Foreign countries; Irish; Travel; dept.eng; faculty_collection

Margaret Fuller: Essays on American Life and Letters - Fuller, Margaret; Myerson, Joel (Masterworks of literature series, 1978)
Keywords: dept.eng; faculty_collection

Tales of the Northwest - Snelling, William Joseph (Masterworks of literature series, 1975)
Keywords: Fiction; Indians of North America; dept.eng; faculty_collection

Edgar Huntly; or, Memoirs of a Sleepwalker. - Brown, Charles Brockden (Masterworks of literature series, 1973)
Keywords: dept.eng; faculty_collection

The Bread-Winners. - Hay, John (Masterworks of literature series ; M-36, 1973)
Keywords: dept.eng; faculty_collection

A Narrative of the Life of David Crockett, of the State of Tennessee. - Crockett, Davy; Arpad, Joseph J. (Masterworks of literature series, 1972)
Keywords: Crockett, Davy, 1786-1836; Creek War, 1813-1814; Tennessee; History; dept.eng; faculty_collection

The Voice of the People, - Glasgow, Ellen; Godshalk, William Leigh (Masterworks of literature series, 1972)
Keywords: dept.eng; faculty_collection

Pembroke. - Freeman, Mary Eleanor Wilkins (Masterworks of literature series, 1971)
Keywords: Fiction; New England; dept.eng; faculty_collection

The Power of Sympathy. the Coquette, - Brown, William Hill; Foster, Hannah Webster (Masterworks of literature series, 1970)
Foster, Hannah Webster, 1759-1840. Coquette., Foster, Hannah Webster, 1759-1840. Coquette, or, The history of Eliza Wharton, Foster, Hannah Webster, 1759-1840. History of Eliza Wharton
Keywords: Fiction; Whitman, Elizabeth, 1752-1788; dept.eng; faculty_collection

What is “Grammar”? - Pelosi, Angelo G (The Modern Language Journal, 1973)
Keywords: dept.eng